Geomagnetic field intensity behavior in South America between 400 AD and 1800 AD: First archeointensity results from Argentina - Goguitchaichvili, Avto (2011)
An absolute archeointensity study in Northwest Argentina provided 25 independent geomagnetic field lectures supported by 37 radiometric dates between AD 400 and 1800. The mean, cooling rate and remanence anisotropy corrected archeointensity values obtained in this study range from 36.5±2.6 to 63.1±8.7μT, with corresponding Virtual Axial Dipole Moments (VADMs) from 7.4±0.5 to 12.7±1.8 (1022Am2). Most of the data are concentrated between a relatively narrow interval from 1350 AD to 1550 AD. Three general features may be detected: the time intervals from about AD 1150 to 1350 and 1450 to 1600 are characterized by quite monotonic decay of geomagnetic intensity while some increase is observed from AD 1600 to 1700. The archeointensity decrease from about 17th century seems to be a general characteristic of global geomagnetic field because it was observed at different places worldwide. In the absence of reliable climate variation record for South America it is delicate to make any firm conclusions about the relationship between the Earth's magnetic field and multi-decadal climatic events. However, it is probably not a coincidence that persistent warm climate detected from Patagonia during AD 1200 to 1350 is consistent to geomagnetic intensity decrease revealed in this study.